Ways out of the arms race from the nuclear threat to mutual security : proceedings of the Second International Scientists' Congress, held at Imperial College of Science, Technology & Medicine, University of London, 2-4 December, 1988 - Hassard, John 1953-; Kibble, T. W. B.; Lewis, Patricia (World Scientific, 2014)
"This congress gathers together scientists from all over the world to analyse the problems of, and possible solutions to, the arms race. Speakers: A Arbatov, E Ash, V Baranovsky, P Deák, H-P Dürr, S Elworthy, R Ennals, R Fieldhouse, R Forsberg, V Gamba-Stonehouse, R Garwin, V Goldanskii, F Heisbourg, F von Hippel, D Hodgkin, S Kapitza, T Kibble, A Lecocq, P Lewis, S Lunn, R McNamara, S Oznobischev, J Pike, R Rilling, J Rotblat, R Sagdeev, M Schmidt, J Sharp, P Smoker, P Starlinger, J A Stein, K Subrahmanyam, T Taylor, M-B Theorin, J Thompson, R Trapp & C Voûte."--Publisher's description